Genesis of the television documentary drama in Belarus - Stezhko, Natallia G. (Journal of the Belarusian State University. Journalism, 2019)
The process of genesis and evolution of the television documentary drama in Belarus is considered. The history, the TV  production, the main goals and the objectives of docudramas are studied. It is noted that the origins of docudramas are to be  found in feature films, not in documentary films. All ontological characteristics of a feature film are present in docudrama:  the construction of the script (including exposition, confrontation and resolution of the story), acting, cinematography and  musical design. These are all the elements that are used towards the creation of an artistic image. It is substantiated that TV  docudramas are not a subgenre of documentary film but an independent form of audiovisual production for TV. Extensive  possibilities of docudramas are revealed: with a relatively low budget they tells a story of a real historical event in an imaginative, graphically compelling and emotionally precise way. These qualities are the reason why filmmakers are increasingly  using the arsenal of docudramas in creating television products.
Keywords: television documentary drama; docudrama; TV production; documentary films; feature films; television; reconstruction; chronicle; audiovisual products; TV broadcast